Patients' Rights Fulfillment towards Medicines Information Services; Law Enforcement and Pharmacist Criminal Liability - Dyah Suryani Sulistyaningtyas; Rena Yulia; Mohamad Noor Fajar Al Arif (International Journal of Social Sciences Review, 2022)
This article aims to determine law enforcement towards pharmacists who do not fulfil patients' rights to access medical information services and criminal liability towards pharmacists who do not provide medical information services to patients. This research is normative juridical research using a legal approach. The results obtained in this study show that law enforcement towards pharmacists who do not provide fulfilment of patients' rights to medicines information services. In terms of legal substance, aspects have been regulated in Law Number 36 of 2009 on Health Article 196, Law Number 8 of 1999 on Consumer Protection Article 45 and Article 47, Article 359 and Article 360 of the Criminal Code, Organizational Regulation of the Indonesian Pharmacists Association Number: PO.007/PP.IAI/1822/XI/2020 concerning Assessment Guidelines and Standard Operating Procedures for Handling Violations of the Indonesian Pharmacist Code of Ethics, Indonesian Pharmacists Association. However, from the aspect of the legal structure, it is still not firm enough in its implementation. It is influenced by the culture of the apparatus and society, which still prioritizes using restorative justice methods and does not understand patients' rights in medical information. Related criminal liability for pharmacists who do not provide medical information services has not been implemented as per the existing rules. Implementing existing regulations resolves criminal liability by agreement between both parties, usually by replacing the appropriate medicine and covering the patient's medical expenses.